Load Cell Failure Risk in Tandem Mobile Crane Lifting: A Fuzzy Fault Tree Analysis Approach - Pradana Putra, Fatich; Ardi Nugroho, Priyambodo Nur; Sutrisno, Imam (Institut Teknologi Sepuluh Nopember, 2025)
Load cell is an critical component in the tandem lifting system using a mobile crane that functions to measure the load accurately. Damage to the load cell can cause operational failure and increase the risk of accidents. This study aims to analyze the potential for load cell damage using the Fuzzy Fault Tree Analysis (FFTA) approach. FFTA combines fault tree logic with fuzzy theory to clarify risk assessment. By collecting data from study literature, interviews and historical equipment data, the analysis results obtained that the factors causing load cell damage include overload factors, damage factors to load cell components and environmental factors. And through the FFTA method, namely the damage factor to the load cell component with a weighting value of 0.1840 or 47%. The contribution of this study is to provide a systematic approach to identifying and evaluating the risk of load cell damage, which can be used as a basis for improving inspection programs and preventive maintenance on tandem lifting using a mobile crane. This approach can also support management decision making in improving the reliability and safety of lifting equipment.